Genetic parameter estimation and molecular foundation of Double-yolk eggs trait in white leghorn - Anqi Chen; Xiaoyu Zhao; Haiyan Wang; Xiurong Zhao; Gang Wang; Xinye Zhang; Xufang Ren; Yalan Zhang; Xue Cheng; Xiaofan Yu; Xiaohan Mei; Huie Wang; et al. (Poultry Science)
Double-yolk (DY) eggs refer to the presence of two yolks in an egg, and they are often present in fowl flocks. As abnormal eggs, DY eggs occur frequently in the early stages of egg-laying in hens, as well as in hens with early sexual maturity. In order to understand the inheritant pattern of DY eggs and explore candidate genes associated with DY eggs, we selected over 10,000 white Leghorn (WL) chickens from 4 generations and recorded the data during the egg laying period, including total egg number and the rate of DY egg number during the first 2 months and the period of 18-58 weeks of age (EN2month, EN38, EN58, DY2month, DY38, and DY58), age at first egg (AFE), first egg weight (FEW), and body weight at first egg (BWA). The results of genetic parameter analysis showed that the DY egg rate was a trait with low to medium heritabilities with the values from 0.15 to 0.29. And there were strong positive phenotypic and genetic correlations between DY egg rate and egg production at different age stages, and they were all strongly negatively correlated with AFE. However, the DY egg rate and egg production at different stages had strong positive and negative genetic correlations with BWA and FEW, respectively. We also found that significant differences in these trait values between different generations and cage layers, indicating that generations and cage layers had a certain influence on these traits. Furtherly, we used whole genome-wide association (GWA) analysis to identify genes underlying DY, and 5 candidate genes (EZH2, CNTNAP2, TMEM163, GPC1, and ACMSD) associated with DY2month in WL. Our study improved the understanding of DY eggs in hens, and the genetic parameters of DY eggs, and also provided insights into reducing the production of DY eggs by various selection strategies.